Digital Learning for Young Minds: The Power of Educational Innovation in Early English Reading Mastery - Novitasari, Yesi; Yetti , Elindra; Sumantri, Mohamad Syarif (Elsya : Journal of English Language Studies, 2025)
Despite the growing emphasis on early childhood English literacy, research on the direct impact of educational technology on young learners' reading skills remains limited, particularly in the Indonesian context. Existing studies often focus on conventional teaching methods or generic digital tools without empirically testing the effectiveness of structured educational technology interventions. Addressing this gap, this study investigates how interactive educational technology enhances early English reading skills in preschoolers. Using a quasi-experimental design with a two-group pretest-posttest control setup, the research involved 60 children aged 5–6 years, divided into an experimental group (n=30) exposed to technology-assisted learning and a control group (n=30) using traditional methods. Data were collected through structured observational assessments and analyzed using an Independent Samples Test. Findings revealed a statistically significant improvement in the experimental group’s reading ability, as indicated by a p-value of 0.001 (<0.05), confirming that technology-based interventions effectively enhance young learners' English reading proficiency. This study contributes to the discourse on early literacy by demonstrating the role of digital tools in fostering emergent reading skills through engaging, interactive, and adaptive learning experiences. The results suggest that integrating educational technology in preschool curricula can bridge early literacy gaps and create an enriched learning environment. On a broader scale, these findings support the need for policy revisions in early education, advocating for digital inclusivity and pedagogical innovation to better equip children with foundational literacy skills in an increasingly technology-driven world.